A social-architecture perspective on gut microbiota dynamics and host physiology - Ni, Zhexin; Zhou, Wei; Gao, Yue (Frontiers in Immunology, 2025)
The human gut microbiota, a dynamic consortium of trillions of microorganisms, is increasingly recognized not merely as a metabolic entity but as a structured “microbial society” exhibiting hierarchical organization, cooperative networks, and competitive exclusion. This hypothesis posits that gut microbiota communities operate under principles analogous to social structures, with emergent behaviors that directly impact host health. By integrating recent advances in microbial ecology, spatial omics, and neurogastroenterology, this paper proposes those microbial social dynamics—such as division of labor, territorial specialization, and collective decision-making—mediate critical host functions, including immune regulation, metabolic homeostasis, and cognitive processes. In research or therapy targeting the gut microbiota, safeguard the stability of the microbial society and eschew simplistic, blunt approaches. In short, the gut microbiota behaves like a collective mind, showing tight unity and rapid, fine-tuned adaptation to external cues. Its imbalance breeds disease; its vigor enhances human life.